Patient and Hospital Characteristics Associated with Admission Among Patients With Minor Isolated Extremity Firearm Injuries: A Propensity-Matched Analysis - Arielle C. Thomas, MD, MPH, MS; Regina Royan, MD, MPH; Avery B. Nathens, MD, PhD; Brendan T. Campbell, MD, MPH; Susheel Reddy, MPH; Sarabeth Spitzer, MD; Doulia Hamad, MD; Angie Jang, BA; Anne M. Stey, MD, MSc (Annals of Surgery Open)
Objective:. To quantify the association between insurance and hospital admission following minor isolated extremity firearm injury. Background:. The association between insurance and injury admission has not been examined. Methods:. This was an observational retrospective cohort study of minor isolated extremity firearm injury captured in the Healthcare Cost and Utilization Project State Inpatient and Emergency Department Databases in 6 states (New York, Arkansas, Wisconsin, Massachusetts, Florida, and Maryland) from 2016 to 2017 among patients aged 16 years or older. The primary exposure was insurance. Admitted patients were propensity score matched to nonadmitted patients on age, extremity Abbreviated Injury Score, and Elixhauser Comorbidity Index with exact matching within hospital to adjust for selection bias. A general estimating equation logistic regression estimated the association between insurance and odds of admission in the matched cohort while controlling for sex, race, injury intent, injury type, hospital profit type, and trauma center designation with observations clustered by propensity score-matched pairs within hospital. Results:. A total of 8151 patients presented to hospital with a minor isolated extremity firearm injury between 2016 and 2017 in 6 states. Patients were 88.0% male, 56.6% Black, and 71.7% aged 16 to 36 years old, and 22.1% were admitted. A total of 2090 patients were matched on propensity for admission. Privately insured matched patients had 1.70 higher adjusted odds of admission and 95% confidence interval of 1.30 to 2.22, compared with uninsured after adjusting for patient and hospital characteristics. Conclusions:. Insurance was associated with hospital admission for minor isolated extremity firearm injury.